Does Adipose Tissue Thickness Affect the Duration of Rotator Cuff Operations? - Deniz Çankaya; Hakan Zeybek; Selin Haver; Daghan Dogruyol; Serdar Aktı; Sefa Aktı (Acta Medica Alanya)
Aim: Accurate estimation of operation time will reduce operating room costs and increase patient satisfaction. In recent studies, authors have found that thicker adipose tissue at the operation site is associated with a higher rate of complications. However, there is no study in the literature investigating the effect on operation time of an increase in adipose tissue thickness. This present study hypothesized that thicker adipose tissue in shoulder surgeries would prolong the operation time, therefore the study was planned accordingly.Material and Methods: Preoperative magnetic resonance images of patients applied with rotator cuff repair between 2015 and 2020 were independently evaluated by two observers. The acromial fat thickness was measured as the fat thickness of the operation area, and the scapular fat tissue thickness as the fat thickness of the region relatively far from the operation area. The data obtained were evaluated using multivariate analysis and a binary logistic regression model.Results: Evaluation was made of a total of 106 patients. The mean total operation time was 89±33 mins. The mean acromial fat thickness was 12.2±4.89 mm and the mean scapular fat thickness was 27.9±12.5mm. The increase in acromial fat thickness was determined to have extended the operation time (OR=5.75, 29.21, p<0.05).Conclusion: The thickness of fat tissue in the surgical area is one of the factors affecting operating time. Patients can be informed about the risk of prolonged surgery time and associated complications before surgery and costs can be reduced by optimizing operating room planning. In addition, it should be considered that tendinous pathologies may be more common in individuals with increased adipose tissue thickness and thus contribute to prolonging the operation time.